2022
DOI: 10.1523/jneurosci.1143-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

What Does the Frontopolar Cortex Contribute to Goal-Directed Cognition and Action?

Abstract: Understanding the unique functions of different subregions of primate prefrontal cortex has been a longstanding goal in cognitive neuroscience. Yet, the anatomy and function of one of its largest subregions (the frontopolar cortex) remain enigmatic and underspecified. Our Society for Neuroscience minisymposiumPrimate Frontopolar Cortex: From Circuits to Complex Behaviorswill comprise a range of new anatomic and functional approaches that have helped to clarify the basic circuit anatomy of the frontal pole, its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…Treatment with Cy5-antagomiR treatment dose-dependently increased Cy5 fluorescence. As the frontal cortex and hippocampus are cognition-related central regions in the brain (Christensen et al, 2022; Hogeveen et al, 2022; Price & Duman, 2020; Sakimoto et al, 2021) , we confirmed IR and antagomiR effects in the frontal cortex and hippocampus. Consistent with in vitro results (Fig.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Treatment with Cy5-antagomiR treatment dose-dependently increased Cy5 fluorescence. As the frontal cortex and hippocampus are cognition-related central regions in the brain (Christensen et al, 2022; Hogeveen et al, 2022; Price & Duman, 2020; Sakimoto et al, 2021) , we confirmed IR and antagomiR effects in the frontal cortex and hippocampus. Consistent with in vitro results (Fig.…”
Section: Resultssupporting
confidence: 73%
“…Cognition is a complex mental process that involves the acquisition, processing, and application of knowledge (Harvey, 2019; Jessen et al, 2020) . The frontal cortex and hippocampus are two critical regions of the brain that play a key role in cognition, including memory, attention, and decision-making (Christensen et al, 2022; Hogeveen et al, 2022; Price & Duman, 2020; Sakimoto et al, 2021) . Cognitive impairment is a common feature of many psychiatric diseases, such as schizophrenia (Gebreegziabhere et al, 2022; Jauhar et al, 2022) and major depressive disorder (Douglas et al, 2018; Wen et al, 2022) , and can significantly impact an individual’s quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies mostly applied an 80 % individual resting motor threshold, recent studies suggested higher doses for proper stimulation conditions. That’s why, we applied a 100 % individual resting motor threshold [Hogeveen et al, 2022a]. To find stimulation sites, we used the 10-20 EEG international system.…”
Section: Methodsmentioning
confidence: 99%
“…The second line of research comes from studies that showed the dissociable role of the right frontopolar cortex (rFPC) and dorsolateral prefrontal cortex (rDLPFC) in controlling direct and random exploration, respectively. Previous neuroimaging studies showed that rFPC drives information-seeking and direct exploration [Badre et al, 2012, Hogeveen et al, 2022a, Mansouri et al, 2017, Tomov et al, 2020], while rDLPFC drives random exploration [Jahn et al, 2023, Tomov et al, 2020]. Moreover, transcranial magnetic stimulation (TMS) over the rFPC decreases direct exploration while intact random exploration [Zajkowski et al, 2017b].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has implicated both the frontopolar cortex (medial prefrontal cortex, Brodmann Area 10) and the amygdala in substance-associated plasticity through the prefrontal-limbic system [2]. The amygdala is critical in responses to affective stimuli, and the frontopolar cortex is thought to be involved in tasks that require control of cognition and action [3]. Amygdala-frontopolar coupling is also recognized as a marker of early relapse risk in people with SUDs [4].…”
Section: Introductionmentioning
confidence: 99%